The growth process in a "dual" economic system - LUTZ, V.C. (PSL Quarterly Review, 2014)
It may be said that the Italian economy has remained - after about three quarters of a century of industrial development along modern lines - roughly half “advanced” and half “primitive”. The historical explanation for this dualism, which has persisted to a degree not found in other countries, depends on what we believe to be its root cause. Here, the author investigates what is in her view the most plausible explanation of its origin - the wage level. Moreover, some of its most important effects on the present structure of Italy’s economy are analysed. Finally, certain special aspects of the problem of economic growth that arise in the dual system are examined. JEL: O11, O14, O52, E24